Pengaruh Brand Ambassador, Brand Awareness, dan Iklan Terhadap Keputusan Pembelian Keju Prochiz Gold Series di Jakarta Selatan - Anistya Palupi; Resti Hardini (TRANSEKONOMIKA: AKUNTANSI, BISNIS DAN KEUANGAN, 2025)
This study aims to analyze the impact of Brand Ambassadors, Brand Awareness, and Advertising on the Purchase Decision of Prochiz Gold Series Cheese in the South Jakarta area. A total of 97 respondents were calculated as a sample using the Lemeshow formula. Non-probability sampling method was used to determine the sample, with purposive sampling technique. Research respondents were selected based on the criteria of those who have purchased and used Prochiz Gold Series Cheese, and have an address in South Jakarta. From the analysis, the multiple linear regression model found was Purchase Decision = KP = 0.142BAM + 0.532BAW + 0.312I. This study concludes that separately, Brand Ambassadors have a positive and significant influence on purchasing decisions for Prochiz Gold Series Cheese, because the T-value is greater than the T-table (2.015> 1.98552). Similarly, Brand Awareness also has a positive and significant influence on purchasing decisions for Prochiz Gold Series Cheese, with a T-value greater than the T-table (6.825 > 1.98552). In addition, advertising also has a positive and significant influence on purchasing decisions for Prochiz Gold Series Cheese, as the T-value is greater than the T-table (4.071 > 1.98552).